Expression and Prognostic Significance of Metastasis-Associated Protein 1 in Gastrointestinal Cancer - Li, Pengping; Cao, Wei; Ding, Rui; Cheng, Mengqiu; Xu, Xin; Chen, Sihan; Chen, Bo; Cao, Guodong; Xiong, Maoming (Frontiers in Oncology, 2020)
Background Metastasis-associated protein 1 (MTA1) is considered a transcription regulator significantly associated with prognosis in cancer patients. However, whether MTA1 is a potential prognostic marker of gastrointestinal cancer (GIC) remains controversial. The current meta-analysis was performed to evaluate the usefulness of MTA1 expression in predicting the clinicopathological features and survival in GIC patients. And the results of gastric cancer were verified by immunohistochemistry (IHC). Methods Eligible studies assessing the relationship between MTA1 and GIC by IHC were searched in the PubMed, Ovid, Web of Science, Cochrane, and CNKI databases by multiple search strategies. The STATA 16.0 software was used to pool data and analyze the association of MTA1 with GIC. The expression of MTA1 was examined in 80 GC patients by IHC. SPSS was used for the statistical analyses and survival curves were calculated by the Kaplan–Meier method. Results According to the meta analysis, MTA1 overexpression was tightly associated with tumor size (OR=1.82, 95%CI 1.16-2.84, P=0.009), differentiation (OR=1.71, 95%CI 1.24-2.37, P=0.001), depth of invasion (OR=3.12, 95%CI 2.55-3.83, P<0.001), lymph node metastasis (OR=2.99, 95%CI 2.02-4.43, P<0.001), distant metastasis (OR=4.66, 95%CI 1.13-19.24, P=0.034), TNM stage (OR=4.28, 95%CI 2.76-6.63, P<0.001). In addition, MTA1 was related to 1- (RR=2.48, 95%CI 1.45-4.25, P=0.001), 3- (RR=1.66, 95%CI 1.30-2.11, P<0.001) and 5-year (RR=1.73, 95%CI 1.37-2.20, P<0.001). In subgroup analysis according to language and tumor type, we reached similar conclusions. Further validation by IHC yielded similar conclusions. Tumor size (P=0.008), lymphatic metastasis (P=0.007) and distant metastasis (P=0.023) were significantly associated with high overexpression of MAT1 in GC patients. And MTA1 expression (HR=2.061, 95%CI 1.066-3.986, P=0.032) were significantly correlated with OS in GC patients, suggesting that MTA1 expression may be an independent prognostic factor for GC. Finnaly, we verified the expression and prognosis of MTA1 in 80 gastric cancer tissues. Conclusions MTA1 is tightly associated with metastasis-related factors, and may constitute a promising prognostic factor of GIC.